Pneumomediastinum complicating pulmonary tuberculosis with diabetic ketoacidosis - Bruno Mendonça Protásio; Jamile Rosário Kalil; João Gabriel Rosa Ramos; Eberth Alves Machado Neto; Alex Teixeira Guabiru; Vilma Takayasu (University of São Paulo, 2011)
We report a case of a 43-year-old man, previously healthy, with a three-month history of weight loss, dyspnea, cough, hemoptysis and chest pain, followed by polyuria and polydipsia during the last weeks. Clinical investigation disclosed diabetic ketoacidosis, pulmonary tuberculosis and pneumomediastinum. The patient's outcome was favorable after clinical treatment and the pneumomediastinum resolved spontaneously without specific intervention.